Midtrimester Cervicovaginal Microbiota: Identification of Microbial Variations Associated with Puerperal Infection at Term - Subramaniam, Akila; Ptacek, Travis; Lobashevsky, Elena; Cliver, Suzanne; Lefkowitz, Elliot J.; Morrow, Casey D.; Biggio, Joseph R., Jr; Edwards, Rodney K. (American Journal of Perinatology, 2016)
Objective This study aims to evaluate differences in the midtrimester cervicovaginal microbiota between women who developed puerperal infections at term and those who did not, and whether obesity modulates this relationship.Methods Previously, cervicovaginal swabs were collected at 21 to 25 weeks gestation (stored at −80°C). Samples were identified from Black women with normal vaginal flora (Nugent score: 0–2) delivering term singletons. Patients were in one of four equally sized groups (total n = 120) characterized by absence or presence of puerperal infection and maternal obesity. Samples were thawed, DNA extracted, and polymerase chain reaction with primers targeting the 16S rDNA V4 region was used to prepare an amplicon library sequenced and analyzed using Quantitative Insights into Microbial Ecology (QIIME) suite. Microbiota differences were assessed using permutation-based anodis over three β-diversity measures; Kruskal–Wallis test was used for taxa level analysis.Results After quality control measures, 113 samples were analyzed. Overall, there was significant clustering by puerperal infection (p = 0.03), but not by obesity (p > 0.05). Detailed taxa level analysis revealed approximately 66% less Proteobacteria phylum and 400% more BVAB1 genera in the second-trimester microbiota of women who had puerperal infections at term (p < 0.05).Conclusion Women who develop puerperal infections at term have a significantly altered midtrimester cervicovaginal microbiome with less Proteobacteria and greater BVAB1. This finding may represent a potential method to identify women at an increased risk of puerperal infection.
Keywords: cervicovaginal microbiome; chorioamnionitis; endometritis; maternal obesity; pregnancy